Analysis of Causal Factors of Hepatitis B in Pregnant Women: Literature Review - Mimi Mauliza; Cut Abyat; marniati marniati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Hepatitis B is a viral infection that affects the liver and is transmitted through contact with blood and other bodily fluids. Pregnant women who contract hepatitis B are at risk of passing the virus to their unborn child during pregnancy or childbirth. This vertical transmission is a major contributor to the high prevalence of hepatitis B in many developing countries. The objective of this study is to examine the factors that contribute to hepatitis B infection in pregnant women, focusing on demographic characteristics, behavioral patterns, and access to healthcare services. Employing a quantitative method with a cross-sectional design, the study found that factors such as low educational attainment, a history of using unsterile needles, previous blood transfusions, and limited knowledge about hepatitis B significantly increase the risk of infection.Therefore, educational approaches and enhanced hepatitis B screening in pregnant women are necessary efforts to prevent transmission